1998
DOI: 10.1152/ajpheart.1998.274.4.h1211
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of heart rate, arterial pressure, and muscle sympathetic nerve activity in normal humans

Abstract: We investigated the frequency components of fluctuations in heart rate, arterial pressure, respiration, and muscle sympathetic nerve activity (MSNA) in 11 healthy women using an autoregressive model and examined the relation among variables using Akaike’s relative power contribution analysis with multivariate autoregressive model fitting. Power spectral analysis of MSNA revealed two peaks, with low-frequency (LF) and high-frequency (HF) components. The LF component of MSNA was a major determinant of the LF com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 23 publications
0
29
1
Order By: Relevance
“…For example, LF SBP has been shown to increase during sympathetic activation, including orthostatic stress, such as lower body negative pressure (7,41,52) and upright tilt (9,20), infusion of vasoactive drugs such as nitroprusside (41), and hypovolemia (26). Similarly, LF SBP power has been shown to decrease significantly during ganglionic blockade in normal subjects (15,32,56) and in patients with essential hypertension and multiple system atrophy (15), indicating that it is largely mediated by the sympathetic nervous system. Finally, LF SBP and LF MSNA power exhibited similar increases and decreases during pharmacological infusions of sodium nitroprusside and phenylephrine, respectively (36), and coherence analysis has quantifiably demonstrated that patterns in LF SBP and LF MSNA are correlated at baseline (18,20) and during HUT in humans (20), whereas HF SBP and HF MSNA are not highly correlated (18).…”
Section: Lf Sbp -Lf Spike Rate Relationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, LF SBP has been shown to increase during sympathetic activation, including orthostatic stress, such as lower body negative pressure (7,41,52) and upright tilt (9,20), infusion of vasoactive drugs such as nitroprusside (41), and hypovolemia (26). Similarly, LF SBP power has been shown to decrease significantly during ganglionic blockade in normal subjects (15,32,56) and in patients with essential hypertension and multiple system atrophy (15), indicating that it is largely mediated by the sympathetic nervous system. Finally, LF SBP and LF MSNA power exhibited similar increases and decreases during pharmacological infusions of sodium nitroprusside and phenylephrine, respectively (36), and coherence analysis has quantifiably demonstrated that patterns in LF SBP and LF MSNA are correlated at baseline (18,20) and during HUT in humans (20), whereas HF SBP and HF MSNA are not highly correlated (18).…”
Section: Lf Sbp -Lf Spike Rate Relationmentioning
confidence: 99%
“…The HF range of the BP variability contains the range of frequencies associated with normal breathing rhythms. Ganglionic blockade has little or no effect on HF BP , suggesting that these oscillations are unrelated to the sympathetic activity and primarily due to changes in intrathoracic pressure caused by the mechanical aspects of respiration (15,32,56).…”
Section: Hf Sbp -Hf Resp Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…The augmentation in LF ABP power appears to be synchronized with the efferent discharge of muscle sympathetic nerve activity [25,35] and is diminished by ·-adrenoceptor antagonists [2,22,35], ganglion blockade [38], or aortic and carotid sinus denervation [5]. Since this LF ABP oscillation, termed Mayer or vasomotor wave [29], is not affected by either heart rate or respiratory pattern [26,37], the increase in LF ABP variability has been related to sympathetically mediated tonic vasomotion.…”
Section: Introductionmentioning
confidence: 99%
“…29 However, recent laboratory studies of the spectral analysis of heart rate, arterial pressure, and muscle sympathetic activity in normal humans found that propranolol (0.2 mg/kg iv) increases burst incidence from 19.0±2.7 to 28.1±2.3 bursts/100 heartbeats. 30 The discrepancies between studies of the effect of propranolol are likely to be related to differences in propranolol dosage.…”
Section: Potential Mechanismsmentioning
confidence: 99%